A halogen-bonding-catalysed Nazarov cyclisation reaction. Issue 57 (27th June 2019) - Dreger, Alexander; Wonner, Patrick; Engelage, Elric; Walter, Sebastian M.; Stoll, Raphael; Huber, Stefan M.
Abstract : Various neutral, mono- and dicationic halogen bond donors were screened for their ability to act as catalysts in a Nazarov cyclisation reaction. Abstract : Various neutral, mono- and dicationic halogen bond donors were screened for their ability to act as catalysts in a Nazarov cyclisation reaction. Using a highly preorganized dicationic catalyst with a noncoordinating counterion proved essential for high activity.